Preparation of acetate peels of valves from the Ocean Quahog, Arctica islandica, for age determinations - Ropes, John W.; United States. National Marine Fisheries Service. (Seattle, Wash. : U.S. Dept. of Commerce, National Oceanic and Atmospheric Administration, National Marine Fisheries Service, 1987)
Mode of access: Internet.